Body image of the elderly in the reflex of self-care for healthy aging: A social-poetic study - Silva, Aila C. dos Santos; Santos, Iraci dos; Berardinelli, Lina Márcia Miguéis (Online Brazilian Journal of Nursing, 2010)
<!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> This work aims at analyzing the elderly imaginative dimension on self-care with a view to a healthy aging process. Social-poetic method, upon sensitivity dynamics of the body as a minimum territory, developed by participants from the Rio de Janeiro State University in 2009. The data generated were analyzed in the light of Nola Pender’s Health Promotion Theory. <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> In the results, the following categories stand out: Caretaking, acknowledging body dimension value; Body displaying obesity trends versus control of chronic diseases; Caretaking and the reflex in the mirror, confirming Pender’s Model Diagram as for behaviors, commitment and personal responsibility, perceived barriers for the adoption of self-care, social and emotional factors predisposed to carelessness, efficacy to adopt strategies favorable to quality of life. <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The conclusion is that the elderly people manifested their concern about carelessness with the body in its physical, intellectual/emotional, social-spiritual dimensions, pointing out the vulnerability for chronic diseases, which is a major public health care issue nowadays.